Компетентнісний аспект фахового навчання майбутніх учителів музичного мистецтва - Чень Яньїн; Chen Yanying (Видавництво «Код», 2025)
Резюме. У статті актуалізовано необхідність удосконалення компетентнісного виміру фахового навчання майбутніх учителів музичного мистецтва. Розкрито сутність компетентнісного підходу, висвітлено та узагальнено погляди науковців щодо компетентності фахівця. Визначено зміст фахових компетентностей майбутнього вчителя музичного мистецтва, окреслено значення мистецької компетентності у процесі формування його особистості, конкретизовано сутність та подано авторське розуміння означеного поняття.

Abstract. The purpose of the article is to summarize the views of scientists on the professional training of future teachers of music on the basis of a competency-based approach, the result of which is the formation of professional competencies. The relevance of the study is determined by the necessity to improve the competency dimension of the professional training of future teachers of music. To reveal the competency aspect of professional training of future teachers of music, modern scientific research has applied methods of scientific and theoretical analysis, systematization, and generalization. The article reveals the essence and content of the competency-based approach in the context of music education, analyzes the interpretation of the concepts of «competence», «professional competence of a future teacher of music art». The views of scientists on the specified problem are highlighted and generalized. It has been established that competence is considered as a result of educational activities. The musical and pedagogical orientation of the professional training of future teachers of music art is emphasized, and the specifics of their future professional activity are revealed. As a result of the analysis and generalization of scientific literature, the content of the professional competencies of future teachers of music was determined, the essence of the artistic competence of future teachers of music was specified, its place within the framework of professional competencies of a teacher-musician and its special role in the formation of his personality were outlined. The author’s understanding of the concept as an integrative characteristic of a specialist is presented, reflecting his readiness and ability for effective musical and pedagogical activity. The principle of interdisciplinary integration, aimed at the formation of a competent teacher of the artistic field, is emphasized.
Competency aspect of professional training of future music teachers
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: компетентнісний підхід; фахове навчання; фахові компетентності; мистецька компетентність; майбутні вчителі музичного мистецтва; музичнопедагогічна діяльність